Pneumococcal meningitis: epidemiological profile pre- and post-introduction of the pneumococcal 10-valent conjugate vaccine - Tatiane E. Hirose; Eliane M.C.P. Maluf; Cristina O. Rodrigues (Elsevier, 2015)
OBJECTIVES: To evaluate the possible effects of the introduction of the pneumococcal conjugate 10-valent vaccine schedule in the state of Parana on pneumococcal meningitis cases and to assess the distribution of serotypes among cases. METHOD: Cross-sectional study with retrospective data collection of cases of pneumococcal meningitis in the state of Paraná reported to Sistema de Informação de Agravos de Notificação (SINAN), from 1998 to 2011. A total of 1,339 cases of pneumococcal meningitis were analyzed; 1,205 cases from the pre-vaccine period (1998-2009) were compared to 134 cases from the post-vaccine period (2010-2011). Descriptive and comparative statistical analyses (chi-squared test and prevalence ratio) were performed using JMP 5.1.2 statistical software (JMP Statistical Discovery, North Carolina, USA) and EPI INFO 6 (Centers for Disease Control and Prevention, Georgia, EUA). RESULTS: There was a significant reduction in the mean rates of incidence and mortality in the general population. The analysis of cases in the pre- and post-vaccination periods in the age groups covered by vaccination (younger than 2 years) showed significant reductions in incidence rates (6.01 cases/100,000 to 2.49 cases/100,000 individuals) and mortality (1.85 cases/100,000 population to 0.47 cases/100,000 population), while the mean lethality rate did not change significantly. There was a significant reduction in cases whose serotypes are included in the vaccine (80.7% to 53.3%). CONCLUSION: Even after a short time of use, the 10-valent pneumococcal conjugate vaccine has already had a significant impact in reducing the incidence and mortality of meningitis cases among infants, as well as the reduction of cases whose serotypes are included in the vaccine.